A importância da Educação de Jovens e Adultos (EJA) para o Movimento dos Trabalhadores Rurais Sem Terra (MST): o exemplo da Comuna Irmã Alberta São Paulo-SP - Jofre, Andréia (2011)
This study aimed to examine the education of youth and adults (EJA) into the Movement of Landless Workers (MST) and a proposed new settlement close to major urban centers, called the Commune of the Earth. To carry out this research, we seek to understand at first as this kind of education aimed at young people and adults takes place within the State of São Paulo and later in a movement of struggle for land as the MST. We analyzed statistical data relating to illiteracy among youth and adults of both the city and the countryside was also possible to compare them and come to the conclusion that there is still a large number of illiterates, particularly in the field. We note the efforts of the MST, so that these negative numbers disappear; inspiration in the great educator Paulo Freire and their pedagogy and use of new teaching methods, such as the Cuban literacy method "Yes I Can" are part of efforts to implementation of a quality education for members of the landless. To understand the organization of a commune of the earth, we as a reference from field work, the Commune of Earth Sister Alberta, located in the borough of Perus, in São Paulo. We analyzed the experiences of its settlers and migrants from rural areas and also in the Metropolitan Region of São Paulo, and their prospects for a new life in the commune's land. These perspectives begin with the purchase of a lot more than that a decent home, to the use of land, with farming techniques in the production of food, which will provide not only the livelihood of the resettled families as well as income generation to marketing part of agricultural production to the neighboring settlement. The long way to go is education, however, has yielded excellent results literacy made from the Cuban method "Yes I can young adults and settlers, who were mostly illiterate. In addition, there are great prospects for continuity of education, from primary school completion and until the arrival to the University by some settlers from the Commune